(untitled) (Heritage, 2025)
Based on the archival materials of the Diplomatic Archives of the Ministry of Foreign Affairs of the Republic of France in Paris, this scientific paper presents the attitudes of France towards the political and economic crisis that the SFRY was going through in 1981-1982. For the analysis of the information available to the French diplomacy about the SFRY in this period, the comprehensive note prepared by the French working group made up of representatives of several French ministries and services (defense, foreign affairs, economy, security) is particularly significant, which, among other things, gives us several scenarios how the crisis in SFRY can develop.The formation of the working group is evidence of increased French interest in the SFRY immediately after the death of Josip Broz Tito, in a period when the first cracks in unity were already visible. Based on the abundance of information, the French build a complete picture of the causes and consequences of the relationship between Serbs, Croats and Albanians, while observing the main lines of development of nationalism in all the republics and among all the nations that make up the SFRY. In addition to political and economic factors, as causes and factors that will deepen the crisis, the growth of nationalism, the role of the church and cultural differences are clearly apostrophized as important. What is even more significant for Franco-Yugoslav relations is the noticeable French commitment to analyzing the state of these relations, both economic, military, political, diplomatic, but it is certainly significant that the possibilities for deepening these relations are also pointed out.